Impact of fungal and plant metabolites application on early development stages of pea powdery mildew. Issue 9 (18th March 2019) - Barilli, Eleonora; González‐Bernal, María J; Cimmino, Alessio; Agudo‐Jurado, Francisco J; Masi, Marco; Rubiales, Diego; Evidente, Antonio
Abstract: BACKGROUND: Pea powdery mildew incited by Erysiphe pisi represents a major constraint for pea crops worldwide. Crop protection is largely based on chemical control, although recently a renewed interest in the discovery of natural products as alternatives to synthetic fungicides application has emerged. Thus, 12 bioactive plant and fungal metabolites belonging to different class of natural compounds were evaluated, together with a commercial fungicide, at different concentrations on detached pea leaves for their potential to inhibit spore germination and subsequent stages of fungal growth. The most effective metabolites were tested at different concentrations in planta under controlled conditions to evaluate the level of control achieved by treatments before, concurrently and after pathogen inoculation. Pathogen development was macroscopically scored on whole plants as percentage of disease severity and area under the disease progress curve. RESULTS: Cavoxin, inuloxin C and sphaeropsidin A strongly inhibited E. pisi germination and haustoria formation and reduced colony size. This effect was dose dependent. These results were further confirmed in whole plants by spraying the metabolites on plant leaves for preventive or curative control, which reduced fungal developmental of E. pisi at levels comparable with those obtained by application of the fungicide. CONCLUSIONS: Cavoxin, inuloxin C and sphaeropsidin A have potential as alternatives to synthetic fungicides for the control of crop pathogens of economic importance such as powdery mildew. © 2019 Society of Chemical Industry Abstract : The natural compounds cavoxin, inuloxin C and sphaeropsidin A strongly reduced Erysiphe pisi developmental in planta and could be used as biocontrol agents of pea powdery mildew.